1993
DOI: 10.1177/095632029300400309
|View full text |Cite
|
Sign up to set email alerts
|

Antiherpes Effect of Dextran Sulphate Combined with Acyclovir in vitro and in vivo

Abstract: SummaryThe combined antiviral effect of dextran sulphate (OS, MW 40000) and acyclovir (ACV) on herpes simplex virus type 1 (HSV-1) and pseudorabies virus (PRV) in vitro and on experimental HSV-1 keratitis in rabbits, was studied, Dextran sulphate ilJ' combination with ACV results in synergistic effect,.a,'$ measured by yield ';'.' .~r eduction assay and on herpes",simplex keratitis in rabbits. The better therapeutic effect of the combination was proved by the decreased severity 'of ocular infection and the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Moreover, the inhibitory effect of this complex was much stronger against HSV-2 than against HSV-1. Pancheva (1993) reported that the polysaccharide dextran sulfate inhibited the HSV attachment to the target cells. The efficacy of the combination of the polysaccharide alginate and rhamnolipid PS-17 against HSV replication could be explained with their dual action on HSV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the inhibitory effect of this complex was much stronger against HSV-2 than against HSV-1. Pancheva (1993) reported that the polysaccharide dextran sulfate inhibited the HSV attachment to the target cells. The efficacy of the combination of the polysaccharide alginate and rhamnolipid PS-17 against HSV replication could be explained with their dual action on HSV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Pentosan polysulfate and dextran sulfate also protected mice against the scrapie agent [6], whereas i-carrageenan attained 100 % survival in mice infected with murine cytomegalovirus [7]. Dextran sulfate was also active against HSV-2 in mice [8], but, on the other hand, it was not effective in cats infected with feline leukemia virus [9], and in ducklings infected with duck hepatitis B virus [10].…”
mentioning
confidence: 98%
“…Acyclovir is a purine nucleoside analog of guanosine that is well-known as a highly potent inhibitor of HSV DNA polymerase [18]. Dextran sulfate is an HSV viral entry inhibitor, which can block the interaction between viral envelope proteins and host cellular receptors [19]. These two drugs with different antiviral action modes were used as the "reference drugs".…”
Section: Wogonin Inhibits Hsv-1/2 Replication In Vitromentioning
confidence: 99%